Development analytical method for the determination of hydroxurea (Hydrea) based on the dissociation of the nickel-chromium-azrole-S complex by visible spectrophotometer. (Latakia University Journal -Basic Sciences Series, 2022)
This research deals with a new spectrophotometric method for the determination of hydroxyurea (Hydrea) (HU), which is one of the drugs used to reduce the accompanying effects of many pathological conditions, including thalassemia, sickle cell anemia and as an inhibitor or treatment in some cancerous tumors. This research depend on the dissociation of the complex chromium Azrole-S with nickel.  the optical spectrum of each of the drug and the complex nickel-chromium azrole-S and of both together, was studied, and it was found that the best wavelength in which the absorption is maximum is at 474nm and at pH = 5. It was also found that there is an inverse linear relationship between the absorbance and the concentration of hydroxyurea, and achieved within a range of concentrations (10-100) µg/mL with a correlation coefficient R2 = 0.991, and the molar absorption coefficient was     . The study also showed that the rate of dissociation of the complex relative to the drug is 1:1 and the reproducibility of the method was 98.66% with a standard deviation percentage standard deviation RSD%=4.82% The method used is also characterized by its ease, simplicity and accuracy of  analysis  results, which can be used in the field of drug control.